2020
DOI: 10.5194/wes-2020-122
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Wind turbines in atmospheric flow – FSI simulations with hybrid LES-IDDES turbulence modelling

Abstract: Abstract. In order to design future large wind turbines, knowledge is needed about the impact of aero-elasticity on the rotor loads and performance, and about the physics of the atmospheric flow surrounding the turbines. The objective of the present work is to study both effects by means of high fidelity rotor-resolved numerical simulations. In particular, unsteady computational fluid dynamics (CFD) simulations of a 2.3 MW wind turbine rotor are conducted, this rotor being the largest design with relevant expe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Contrary to this, the coarse mesh provides rather poor wake predictions. Moreover, Grinderslev et al [16] compared the onshore wind turbine aerodynamic performance considering the turbine flexibility under turbulent inflows using LES and IDDES models, his study revealed that there is no significant difference between both methods on the prediction of separate flows and blades deflection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrary to this, the coarse mesh provides rather poor wake predictions. Moreover, Grinderslev et al [16] compared the onshore wind turbine aerodynamic performance considering the turbine flexibility under turbulent inflows using LES and IDDES models, his study revealed that there is no significant difference between both methods on the prediction of separate flows and blades deflection.…”
Section: Introductionmentioning
confidence: 99%
“…Figure16 Turbulence intensity at different axial positions at hub height (Z=90 m) in the wake region at t=0.9T…”
mentioning
confidence: 99%